Novel vector of scrub typhus in subantarctic Chile - evidence from human exposure - Weitzel, Thomas; Silva, María Carolina; Martínez, Constanza; Stekolnikov, Alexandr; Pérez, Caricia; Pérez, Ruth; Vial, Cecilia; Abarca, Katia; Acosta, Gerardo (Clinical Infectious Diseases, 2021)
The exposure of a research team to chigger mites in southern Chile allowed the first identification of a trombiculid species as vector and reservoir of scrub typhus outside the tsutsugamushi triangle, providing unique insights into the ecology and transmission of this recently discovered rickettsial infection in South America. Versión publicada